THE INFLUENCE OF PRICE, LOCATION, AND WORD OF MOUTH ON PURCHASING DECISIONS AT 35.000 CONVENIENCE STORES (Case Study at Cut Kinan Store In Krueng Geukuh, Dewantara District, Aceh Utara Regency) - Riva Hayatunnisa; Adnan; Juli Mursyida; Yuli Asbar (International Journal of Social Science, Educational, Economics, Agriculture Research and Technology (IJSET), 2024)
This study aims to determine how the influence of price, location, and word of mouth on purchasing decisions at the Cut Kinan Store in Krueng Geukuh, Dewantara District, North Aceh Regency. Purchase decisions are measured using indicators consisting of product choice, brand choice, dealer choice, purchase time, and purchase amount. Then the price variable indicators used consist of affordability, price suitability with product quality, price competitiveness, and price suitability with benefits. Meanwhile, location variables use indicators consisting of access, visibility, traffic, parking lots, and expansion. As well as word of mouth variables using indicators consisting of speakers, topics, tools, speaker participation, and supervision. Where all these variables will be measured using an ordinal scale. The data used in this study was primary data obtained by distributing questionnaires to 96 respondents who made purchases at Toko Cut Kinan. The data analysis technique used is multiple linear regression using the help of SPSS software version 26. The results showed that price, location, and word of mouth had a positive and significant effect on purchasing decisions at the Cut Kinan Store in Krueng Geukuh, Dewantara District, North Aceh Regency. Meanwhile, the results of the coefficient of determination test found that purchasing decisions at Cut Kinan Store were influenced by price, location, and word of mouth by 60.8 percent.